Identifikasi Jenis Tanaman Pala (Miristica Fragrans Houtt) di Lokasi Pembibitan Pala di Kota Ternate (Sebagai Bahan Ajar Mata Kuliah Morfologi Tumbuhan: Identification of Nutmeg Plant Types (Miristica Fragrans Houtt) at Nutmeg Nursery Locations in Ternate City (As Teaching Material for Plant Morphology Course) - Tabaika, Rosita; Juniartin, Juniartin; Muna, Lintal; Masita, Alika (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study examines the types, dominance, and income of nutmeg farmers in Ternate, West Halmahera, and Bacan Island, to improve the effectiveness of learning and farmer welfare through more profitable nutmeg nurseries. This study used qualitative descriptive methods and surveys in five locations, with nutmeg nurseries as subjects. Data were collected through observation, interviews, and documentation, then analyzed by tabulation. Based on the study, the most nutmeg varieties in the nursery locations were Ternate 1, found in five locations: Maliaro, Tobololo, Sulamadaha, Loto, and Togafo. Ternate 1 nutmeg is superior because its seeds and maces are of high quality, with characteristics of regular branching, oval leaves, and round fruit. In addition, Makian Lokal and Tobelo 1 varieties are also present, although limited. Pala Gaji, which is only found in Tobololo, has white mace, different from other varieties which are red when ripe. The Ternate 1 variety is the most dominant because many of its parent trees are spread across Ternate. In five sub-districts in Ternate City, there are four nutmeg varieties: Ternate 1, Tobelo 1, Makian Lokal, and Pala Gaji. The Ternate 1 variety is the most dominant. Of the 24 nursery farmers, their income can increase two-fold or more depending on the number of seedlings produced.